Glass cloth, prepreg, and printed wiring boards
By controlling the type and amount of silene coupling agent on silene glass fabrics and using dry ice spray technology to open the fibers, the problem of difficult to reduce the dielectric loss arc of low-dielectric constant glass fabrics in the prior art is solved, and the high thermal resistance and insulation reliability of printed circuit boards are achieved.
Patent Information
- Application Number
- JP2022563227
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-08
- Filing Date
- 2022-10-05
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2042-10-05
AI Technical Summary
The prior art has shortcomings in improving the thermal resistance and dielectric characteristics of printed circuit boards, especially when low-dial constant glass and silene glass are used, it is difficult to effectively reduce the arc of dielectric loss, and traditional fiber opening technology cannot fully open silene glass fabrics with higher hardness.
By controlling the type and amount of silene coupling agent attached to the surface of silene glass and using dry ice spray technology to open the fibers, the dielectric properties and thermal resistance of glass fabrics are improved.
The dielectric loss arc reduction of low-dielectric constant glass fabrics is achieved, which improves the thermal resistance and insulation reliability of printed circuit boards, and avoids the brittleness of silene glass fabrics.
Smart Images

Figure 0007667798000001 
Figure 0007667798000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass cloth, a prepreg, and a printed wiring board. [Background technology]
[0002] Currently, the performance of information terminals such as smartphones is improving, and high-speed communication, as typified by 5G communication, is progressing. In response to this background, not only is there a need for improved heat resistance, which has been conventionally required, but there is also a need for further improvement in the dielectric properties of the insulating material (e.g., lowering the dielectric tangent), particularly for printed wiring boards for high-speed communication. Similarly, there is a background to the need for improved dielectric properties for prepregs used as insulating materials for printed wiring boards, and for the glass yarns and glass cloths contained in the prepregs.
[0003] In order to reduce the dielectric constant of insulating materials, a method is known in which insulating materials are constructed using prepregs in which a low dielectric resin (hereinafter referred to as a "matrix resin") is impregnated into glass cloth (Patent Documents 1 and 2). Patent Documents 1 and 2 state that polyphenylene ether terminally modified with vinyl or methacryloxy groups is advantageous in terms of low dielectric properties and heat resistance, and that this modified polyphenylene ether is used as a matrix resin.
[0004] Also, a method of constructing a prepreg using low dielectric glass to improve the dielectric properties of the prepreg is known (Patent Document 3). In Patent Document 3, glass yarn with a SiO2 composition amount of 98 mass% to 100 mass% is used. Patent Document 3 also describes a method of constructing a prepreg using a low dielectric glass cloth that is surface-treated with a silane coupling agent having an unsaturated double bond group and meets various requirements such as an ignition loss value of 0.12 mass% to 0.40 mass%. Also, as a coupling agent, for example, aminosilane or aminosilane hydrochloride is known (Patent Document 4).
[0005] Furthermore, Patent Documents 5 and 6 report a glass cloth opening technique using water jet or other water flow pressure, and a glass cloth opening technique using ultrasonic waves or the like. By subjecting glass cloth to opening treatment, it becomes possible to make it difficult for bubbles called voids to occur in prepregs and printed wiring boards. By reducing voids, the heat resistance and insulation of printed wiring boards can be improved, and therefore the opening treatment process is known to be important in the glass cloth manufacturing process. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2019 / 065940 [Patent Document 2] International Publication No. 2019 / 065941 [Patent Document 3] JP 2018-127747 A [Patent Document 4] JP 2016-98135 A [Patent Document 5] JP 2009-263824 A [Patent Document 6] JP 2020-158945 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, Patent Documents 1 and 2 leave room for further improvement in dielectric properties. For example, Patent Documents 1 and 2 do not consider the use of low dielectric glass as described in Patent Document 3. Patent Document 3 also describes that glass with an SiO2 composition amount of 98 mass % to 100 mass % is problematic from the practical viewpoint, and therefore, there has been a need for another method for suitably providing glass cloth and therefore prepreg using this type of glass yarn.
[0008] In addition, when the aminosilane or aminosilane hydrochloride described in Patent Document 6 is used as a silane coupling agent, peeling easily occurs at the interface between the glass cloth and the matrix resin, which results in a problem that it is difficult to ensure various properties. Furthermore, there is room for further study in terms of further improving the dielectric properties of the glass cloth described in Patent Document 4. In other words, there has been a need for a new method for lowering the dielectric tangent of glass cloth, other than the method of reducing the silanol groups present on the surface of the glass cloth as pointed out in Patent Document 4. Furthermore, since quartz glass is harder than glasses other than quartz glass, the inventors have found that glass cloth made of quartz glass yarn cannot be sufficiently opened by the conventional opening treatment described in Patent Documents 5 and 6.
[0009] Therefore, the present invention aims to provide a glass cloth and a prepreg that can preferably obtain the advantages of low dielectric glass, typically quartz glass cloth, and surface treatment of glass yarns with a specific silane coupling agent, and can improve dielectric properties (e.g., reduce dielectric tangent). Another object of the present invention is to provide a printed wiring board, an integrated circuit, and an electronic device that can improve insulation reliability and heat resistance by using a glass cloth that has been processed to open fibers more easily than before. Another object of the present invention is to provide a method of processing glass to preferably obtain the above glass cloth. [Means for solving the problem]
[0010] The present inventors have conducted extensive research to solve the above problems, and have focused on the type and amount of silane coupling agent chemically bonded to the surface of low dielectric glass when the glass thread is used. They have found that controlling the type and amount of silane coupling agent chemically bonded to the surface of the glass makes it possible to suitably reduce the dielectric tangent of the glass cloth while ensuring the heat resistance of the resulting printed wiring board. They have also found that opening the glass cloth, for example, by dry ice blasting, makes it possible to improve the insulation reliability and heat resistance of the printed wiring board while reducing the amount of silane coupling agent attached, and have arrived at the present invention. Some aspects of the present invention are exemplified below. [1] A glass cloth made by weaving glass yarn, The bulk dielectric tangent of the glass constituting the glass yarn is 0.0010 or less; The ignition loss value of the glass cloth is 0.01% by mass or more and less than 0.12% by mass, The glass cloth has a void count of 180 or less 5 minutes after being impregnated with castor oil. [2] 2. The glass cloth according to item 1, wherein the void reduction rate of the glass cloth after 1 minute to 5 minutes from impregnation with castor oil is 70% or more. [3] A glass cloth made by weaving glass yarn, The bulk dielectric tangent of the glass constituting the glass yarn is 0.0010 or less; The ignition loss value of the glass cloth is 0.01% by mass or more and less than 0.12% by mass, The glass cloth has a void reduction rate of 70% or more after 1 minute to 5 minutes when the glass cloth is impregnated with castor oil. [4] 3. The glass cloth according to item 1 or 2, wherein the number of voids in the glass cloth after 5 minutes of being impregnated with castor oil is 160 or less. [5] 4. The glass cloth according to item 2 or 3, wherein the void reduction rate of the glass cloth after 1 minute to 5 minutes from impregnation with castor oil is 80% or more. [6] 6. The glass cloth according to any one of items 1 to 5, wherein the bulk dielectric tangent of glass constituting the glass yarns is 0.0008 or less. [7] 7. The glass cloth according to any one of items 1 to 6, wherein the silicon (Si) content in the glass yarn is 95.0% by mass to 100% by mass in terms of silicon dioxide (SiO2). [8] 8. The glass cloth according to any one of items 1 to 7, wherein the silicon (Si) content in the glass yarn is 99.0% by mass to 100% by mass in terms of silicon dioxide (SiO2). [9] 9. The glass cloth according to any one of items 1 to 8, which has been surface-treated.
[10] The surface treatment is carried out according to the following general formula (1): X(R) 3-n SiY n (1) (In the formula, X is an organic functional group having one or more unsaturated double bond groups having radical reactivity, Each Y is independently an alkoxy group; n is an integer from 1 to 3, Each R is independently at least one group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group. 10. The glass cloth according to item 9, which is treated with a silane coupling agent having a structure represented by:
[11] Item 11. The glass cloth according to item 10, wherein X in the general formula (1) does not contain an amino group and has a (meth)acryloxy group.
[12] 12. The glass cloth according to any one of items 1 to 11, wherein the ignition loss value of the glass cloth is 0.10% by mass or less.
[13] 13. The glass cloth according to any one of items 1 to 12, having a nitrogen content per mass of less than 0.004 mass %.
[14] 14. The glass cloth according to any one of items 1 to 13, wherein the dielectric tangent of the glass cloth at 10 GHz measured by a resonance method is more than 0 and not more than 0.0008.
[15] 15. The glass cloth according to any one of items 1 to 14, having a dielectric loss tangent at 10 GHz of more than 0 and not more than 0.0005, as measured by a resonance method.
[16] 16. A prepreg comprising the glass cloth according to any one of items 1 to 15 and a matrix resin impregnated into the glass cloth.
[17] 17. The prepreg according to item 16, further comprising an inorganic filler.
[18] Item 18. A printed wiring board comprising the prepreg according to item 16 or 17.
[19] Item 19. An integrated circuit comprising the printed wiring board according to item 18.
[20] Item 19. An electronic device comprising the printed wiring board according to item 18. Effect of the Invention
[0011] According to the present invention, it is possible to provide a glass cloth and a prepreg that can preferably obtain the advantages of low dielectric glass and surface treatment of glass yarns with a specific silane coupling agent, and can improve dielectric properties (for example, reduce dielectric tangent). Furthermore, according to the present invention, it is also possible to provide a printed wiring board, an integrated circuit, and an electronic device that can improve heat resistance by using the prepreg. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Below, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described, but the present invention is not limited to this embodiment, and various modifications are possible without departing from the gist of the present invention.
[0013] In this embodiment, a numerical range described using "~" represents a numerical range including the numerical values before and after "~" as the lower and upper limits. In addition, in this embodiment, in a numerical range described in stages, the upper limit or lower limit described in a certain numerical range can be replaced with the upper limit or lower limit of another numerical range described in stages. Furthermore, in this embodiment, the upper limit or lower limit described in a certain numerical range can also be replaced with a value shown in the examples. And, in this embodiment, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes, as long as the function of the process is achieved.
[0014] [Glass cloth] [Overall structure] The glass cloth according to the present embodiment is a glass cloth formed by weaving glass yarns, in which the bulk dielectric tangent of the glass constituting the glass yarns is 0.0010 or less, the ignition loss value of the glass cloth is 0.01% by mass or more and less than 0.12% by mass, and the number of voids after 5 minutes when the glass cloth is impregnated with castor oil is 180 or less. Furthermore, the void reduction rate after 1 minute to 5 minutes when the glass cloth is impregnated with castor oil is preferably 70% or more. The second glass cloth according to the present embodiment is a glass cloth obtained by weaving glass yarns, in which the bulk dielectric tangent of the glass constituting the glass yarns is 0.0010 or less, the ignition loss value of the glass cloth is 0.01% by mass or more and less than 0.12% by mass, and the void reduction rate after 1 minute to 5 minutes when impregnated with castor oil is 70% or more. In addition, it is preferable that the number of voids in the glass cloth after 5 minutes from the time of impregnation with castor oil is 160 or less, and it is preferable that the void reduction rate in the glass cloth after 1 to 5 minutes from the time of impregnation with castor oil is 80% or more.
[0015] This makes it possible to provide a glass cloth and a prepreg that can improve the dielectric properties (for example, a reduction in the dielectric tangent) and improve the heat resistance and insulation reliability of a printed wiring board. According to this embodiment, the glass cloth can be obtained that has a dielectric tangent close to the bulk dielectric tangent of glass.
[0016] The glass cloth according to the present embodiment can be produced by weaving glass yarns (e.g., glass yarns consisting of a plurality of glass filaments) as warp and weft yarns. Examples of the weaving structure of the glass cloth include plain weave, sash weave, satin weave, and twill weave. Among these, the plain weave structure is preferred.
[0017] The weft density of the warp and weft yarns constituting the glass cloth according to the present embodiment is preferably 10 yarns / inch to 120 yarns / inch (=10 to 120 yarns / 25.4 mm), more preferably 40 yarns / inch to 100 yarns / inch. When the weft density is within the above range, the effects of the present invention can be easily obtained.
[0018] The basis weight (mass of the glass cloth) of the glass cloth according to this embodiment is preferably 8 g / m 2 ~250g / m 2 and more preferably 8 g / m 2 ~100g / m 2 and more preferably 8 g / m 2 ~80g / m 2 and particularly preferably 8 g / m 2 ~50g / m 2 When the basis weight of the glass cloth is within the above range, the effects of the present invention are easily obtained.
[0019] [Glass thread] The glass yarn constituting the glass cloth according to the present embodiment is obtained by using low dielectric glass as a raw material. Specifically, the bulk dielectric tangent of the glass constituting the glass yarn is 0.0010 or less. By using such glass yarn, the dielectric properties of the obtained glass cloth can be improved. From the viewpoint of improving the dielectric properties of the obtained glass cloth, the bulk dielectric tangent of the glass is preferably 0.0008 or less, more preferably 0.0006 or less, even more preferably 0.0005 or less, and particularly preferably 0.0003 or less.
[0020] The glass yarn having a bulk dielectric tangent in the range of 0.0010 or less has a Si content in the range of 95.0 mass% to 100 mass%, more preferably 99.0 to 100 mass%, further preferably 99.5 to 100 mass%, particularly preferably 99.9 to 100 mass%, calculated as SiO2. By using such glass yarn, the dielectric properties of the obtained glass cloth can be improved.
[0021] The bulk dielectric tangent of the glass constituting the glass cloth of the present embodiment is in the range of 0.0010 or less, more preferably in the range of 0.0008 or less, further preferably in the range of 0.0005 or less, and particularly preferably in the range of 0.0004 or less. The bulk dielectric tangent of the glass constituting the glass cloth can be measured by the method described in the Examples.
[0022] The average filament diameter of the glass filaments constituting the glass yarn is preferably 2.5 μm to 9.0 μm, more preferably 2.5 μm to 7.5 μm, even more preferably 3.5 μm to 7.0 μm, even more preferably 3.5 μm to 6.0 μm, and particularly preferably 3.5 μm to 5.0 μm. If the filament diameter is less than the above value, the filament breaking strength is low, and the resulting glass cloth is likely to generate fluff. If the filament diameter exceeds the above value, the mass of the glass cloth is large, and it is difficult to transport or process it. If the average filament diameter of the glass filaments is within the above range, the effects of the present invention are easily obtained.
[0023] In the glass cloth according to the present embodiment, the glass yarn is preferably surface-treated from the viewpoint of improving adhesion with the resin used in the prepreg. The glass yarn can be surface-treated with, for example, a titanate coupling agent or a silane coupling agent, and is preferably surface-treated with a silane coupling agent from the viewpoint of facilitating modification with a functional group suitable for each resin of the prepreg. The nitrogen content per mass of the glass cloth is preferably less than 0.004% by mass. Such a nitrogen content is based on, for example, the amount of a component containing an amino group in a silane coupling agent. The nitrogen content per mass of the glass cloth may be 0 or more.
[0024] [Silane coupling agent] The silane coupling agent used in the present embodiment is represented by the following general formula (1): X(R) 3-n SiY n (1) (In the formula, X is an organic functional group having one or more unsaturated double bond groups having radical reactivity, Each Y is independently an alkoxy group; n is an integer from 1 to 3, Each R is independently a group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group. It is preferable that the glass cloth has a structure represented by the following formula: By surface-treating the glass cloth with the silane coupling agent represented by the general formula (1), it becomes easier to improve the insulation reliability and heat resistance of the printed wiring board.
[0025] In addition, it is preferable that X in the molecular structure of the silane coupling agent of the general formula (1) does not contain an amino group and has a (meth)acryloxy group. A silane coupling agent that contains an extremely small amount of a component containing an amino group or does not contain an amino group is highly hydrophobic. By surface-treating a glass thread, which is a low dielectric glass, with such a highly hydrophobic silane coupling agent, peeling at the interface between the obtained glass cloth and the matrix resin can be suppressed, and as a result, various properties including dielectric properties (e.g., insulating properties) can be improved. In this specification, both the case where the glass filament is surface-treated with a silane coupling agent and the case where the glass cloth is surface-treated with a silane coupling agent are included in the concept that the glass thread is surface-treated with a silane coupling agent. There is no particular limitation on the method for evaluating whether or not an amino group is contained, but a method using gas chromatography is known. It is possible to determine whether or not the silane coupling agent contains an amino group by measuring the amount of nitrogen dioxide generated by thermal decomposition using gas chromatography. Specifically, if the nitrogen content per mass of the glass cloth is less than 0.004 mass%, it can be determined that the silane coupling agent does not contain an amino group. The nitrogen content per mass of the glass cloth may be 0 or more. When the silane coupling agent contains an extremely small amount of a component containing an amino group or does not contain such a component, depending on the measurement method, the "content of the component containing an amino group in the silane coupling agent" and therefore the "nitrogen content per mass of the glass cloth" may be derived as a negative value due to baseline disturbance or the like. However, even in this case, if the nitrogen content per mass of the glass cloth is considered to be a small amount, it is included in the concept of "less than 0.004 mass%".
[0026] Here, the present inventors have speculated that one of the causes of the increase in the dielectric tangent of the glass cloth is unnecessary components that remain physically attached to the surface of the glass yarn without forming a chemical bond with the surface of the glass yarn. Examples of unnecessary components include residues or modified products of silane coupling agents that remain physically attached to the surface of the glass yarn without forming a chemical bond with the surface of the glass yarn and cannot be completely washed off. From the viewpoint of suppressing the remaining and generation (modification) of unnecessary components that should be reduced from the surface of the glass yarn, it is preferable that X in the general formula (1) is an organic functional group that does not contain an amino group and has one or more unsaturated double bond groups having radical reactivity.
[0027] X in the general formula (1) does not contain an amino group. For example, it is preferable that X in the general formula (1) does not contain an amine such as a primary amine, a secondary amine, or a tertiary amine, or an ammonium cation such as a quaternary ammonium cation. This makes it possible to suitably control the amount of the silane coupling agent that chemically bonds with the surface of the glass yarn, and to suitably improve the dielectric properties of the glass cloth. In addition, the heat resistance of the resulting printed wiring board can be ensured.
[0028] For the purpose of stabilizing the treatment of the glass cloth, it is preferable that in the general formula (1), at least one of the multiple Y's is an alkoxy group having 1 to 5 carbon atoms (an alkoxy group having 1, 2, 3, 4, or 5 carbon atoms). It is more preferable that half or more or all of the multiple Y's are alkoxy groups having 1 to 5 carbon atoms.
[0029] The silane coupling agent represented by the general formula (1) may be used alone or in combination with two or more kinds of silane coupling agents. For example, two or more kinds of silane coupling agents in which X in the general formula (1) is different from each other may be used in combination, or two or more kinds of silane coupling agents in which R in the general formula (1) is different from each other may be used in combination.
[0030] In the silane coupling agent for surface treating the glass yarn, the content derived from the silane coupling agent represented by the general formula (1) is preferably 95.0% by mass to 100% by mass, more preferably 96.5% by mass to 100% by mass, even more preferably 98.0% by mass to 100% by mass, even more preferably 99.0% by mass to 100% by mass, and particularly preferably 99.9% by mass to 100% by mass. This makes it easier to improve various properties including dielectric properties of the obtained glass cloth. The silane coupling agent used in this embodiment may contain a silane coupling agent (other silane coupling agent) other than the silane coupling agent represented by the general formula (1), and may contain components other than the silane coupling agent within the scope of the present invention.
[0031] The molecular weight of the silane coupling agent represented by the general formula (1) is preferably 100 to 600, more preferably 150 to 500, and even more preferably 200 to 450. In particular, it is preferable to use multiple silane coupling agents having different molecular weights within the above range in combination as the silane coupling agent. According to this, the glass yarn can be suitably surface-treated with different types of silane coupling agents, and the density of the silane coupling agent on the glass surface increases. This tends to further improve the reactivity with the matrix resin. When multiple silane coupling agents having different molecular weights are used in combination, it is preferable that at least two of the silane coupling agents are silane coupling agents represented by the general formula (1) and within the above molecular weight range.
[0032] The silane coupling agent represented by the general formula (1) is preferably nonionic. For example, X in the general formula (1) preferably has at least one group selected from the group consisting of a vinyl group and a (meth)acryloxy group, and more preferably has a (meth)acryloxy group. This ensures suitable reactivity with the matrix resin, and makes it easier to improve the heat resistance and reliability of the printed wiring board. The (meth)acryloxy group includes at least one of a methacryloxy group and an acryloxy group.
[0033] As the silane coupling agent represented by the general formula (1), for example, vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 5-hexenyltrimethoxysilane and acryloxypropyltrimethoxysilane are preferred. These silane coupling agents are easy to obtain the effects of the present invention. As the silane coupling agent represented by the general formula (1), including the above, the following silane coupling agents can be mentioned.
[0034] [Table 1]
[0035] [Ignition loss value of glass cloth] Here, the glass cloth according to the present embodiment has an ignition loss value of 0.01% by mass or more and less than 0.12% by mass. This makes it possible to provide a printed wiring board having a lower dielectric tangent while having good insulation properties. The ignition loss value is an index that can indirectly grasp the amount of silane coupling agent that has been surface-treated on the glass cloth, and can be measured in accordance with the method described in JIS R3420.
[0036] The ignition loss value of the glass cloth is preferably 0.01% by mass or more and 0.10% by mass or less, more preferably 0.02% by mass or more and 0.09% by mass or less, and even more preferably 0.03% by mass or more and 0.08% by mass or less. If the ignition loss value exceeds the above value, the amount of silane coupling agent chemically bonded to the surface of the glass yarn tends to be too large, in which case the dielectric tangent of the glass cloth and, in turn, the dielectric tangent of the resulting printed wiring board tend to decrease. On the other hand, if the ignition loss value is less than the above value, the amount of silane coupling agent bonded to the surface of the glass yarn tends to be too small, in which case the heat resistance of the resulting printed wiring board tends to deteriorate.
[0037] In this respect, in this embodiment, as described above, low dielectric glass is used as the glass thread, and the nitrogen content per mass of the glass cloth is preferably less than 0.004 mass%, more preferably less than 0.0035, even more preferably less than 0.003, and particularly preferably less than 0.0025. In general, it has been pointed out that glass cloth using low dielectric glass is prone to brittle fracture due to the high hardness of SiO2. However, in addition to the good compatibility between the low dielectric glass and the type of silane coupling agent that treats it on the surface, the ignition loss value of the glass cloth is within the above range, so that the glass cloth according to this embodiment can reduce the risk of brittle fracture.
[0038] [Method for measuring dielectric tangent of glass cloth] The dielectric properties of the glass cloth according to the present embodiment can be measured using a resonance method. A preferred measuring device using the resonance method is a split cylinder resonator. The resonance method allows simple and accurate measurement compared to the conventional measurement method in which a printed wiring board is prepared as a measurement sample and the dielectric properties are evaluated. The reason for this is that the resonance method is suitable for evaluating low-loss materials in the high frequency range, although not limited by theory. As a method for evaluating dielectric properties other than the resonance method, for example, a lumped parameter method or a reflection transmission method is known. On the other hand, in the lumped parameter method, it is necessary to sandwich the measurement sample between two electrodes to form a capacitor, so the operation is complicated. In addition, in the reflection transmission method, when evaluating a low-loss material, the influence of the matching characteristics of the port is likely to appear, and therefore it is likely to be difficult to evaluate the dielectric tangent of the sample with high accuracy.
[0039] In measuring the dielectric properties of the glass cloth according to the present embodiment, which is applicable to printed wiring boards, particularly printed wiring boards for high-speed communication, the measurable range of the measuring device is preferably within a suitable range for both the frequency dielectric constant (Dk) and the dielectric loss tangent (Df). -1 ~50Fm -1 The range of 1.5Fm is preferred. -1 ~10Fm -1More preferably, the range is 2.0Fm -1 ~5Fm -1 More preferably, Df is in the range of 1.0×10 -6 ~1.0×10 -1 The range of 1.0×10 -5 ~5.0×10 -1 The range of 5.0×10 is more preferable. -5 ~1.0×10 -2 The range is more preferable.
[0040] The measurement equipment is preferably capable of measuring frequencies of 10 GHz or higher, which makes it possible to evaluate the characteristics in the frequency band region expected when the material is actually used as glass cloth for printed wiring boards for high-speed communication.
[0041] The measurement area is 10 mm 2 It is preferable that the thickness is 15 mm or more. 2 More preferably, it is 20 mm or more. 2 It is more preferable that the above is satisfied. By measuring the dielectric properties of the glass cloth over a larger area, the reliability of the test results for the glass cloth can be improved.
[0042] The measurable thickness of the sample is preferably 3 μm to 300 μm, more preferably 5 μm to 200 μm, and even more preferably 7 μm to 150 μm, which can increase the reliability of the inspection results for the glass cloth.
[0043] It is possible to estimate the dielectric tangent of the glass cloth to some extent from the bulk dielectric tangent, and vice versa. On the other hand, there are cases where the dielectric tangent of the glass cloth differs from the bulk dielectric tangent. Although it is not desired to be bound by theory, the causes of this difference include, for example, (1) the generation of thermal oxides and deterioration products of the sizing agent that are physically attached to the surface of the glass yarn, and (2) the remaining and generation of unnecessary components that are physically attached without forming a chemical bond with the surface of the glass yarn and cannot be completely washed off. Therefore, the dielectric tangent of the glass cloth can be controlled within the above range by selecting the type of sizing agent, optimizing various conditions in the manufacturing process of the glass cloth, etc.
[0044] The glass cloth according to the present embodiment has a dielectric loss tangent at 10 GHz, measured by the above-mentioned resonance method, of preferably 0.0008 or less, more preferably 0.0005 or less, even more preferably 0.00045 or less, even more preferably 0.000425 or less, and particularly preferably 0.0004 or less. Such a glass cloth can provide a prepreg capable of improving the dielectric properties.
[0045] [Impregnation of glass cloth] The first glass cloth according to the present embodiment has a void number of 180 or less after 5 minutes when impregnated with castor oil. According to this, since the glass cloth has good impregnation with resin, the insulation and heat resistance of the printed wiring board can be improved. The void number after 5 minutes is preferably in the range of 160 or less, more preferably in the range of 140 or less, even more preferably in the range of 120 or less, even more preferably in the range of 110 or less, and particularly preferably in the range of 100 or less. The smaller the void number after 5 minutes, the better the impregnation, and the stronger the adhesion between the glass cloth and the resin, so that it is possible to provide a printed wiring board having good insulation reliability and heat resistance even if the amount of the surface treatment agent attached to the glass cloth surface is small. In order to make the void number after 5 minutes 180 or less after impregnation with castor oil, for example, the glass cloth is treated with a silane coupling agent represented by the above general formula (1) and a fiber opening method such as dry ice blasting or bending is used.
[0046] The first glass cloth according to this embodiment preferably has a void reduction rate of 70% or more after 1 to 5 minutes of impregnation with castor oil. The reduction rate is preferably in the range of 80% or more, more preferably in the range of 82% or more, even more preferably in the range of 84% or more, even more preferably in the range of 86% or more, and particularly preferably in the range of 88% or more. The number of voids can be measured by the method described in the examples.
[0047] The second glass cloth according to the present embodiment has a void reduction rate of 70% or more after 1 to 5 minutes when impregnated with castor oil. According to this, since the glass cloth has good impregnation with resin, the insulation and heat resistance of the printed wiring board can be improved. The void reduction rate after 1 to 5 minutes is preferably in the range of 80% or more, more preferably in the range of 82% or more, even more preferably in the range of 84% or more, even more preferably in the range of 86% or more, and particularly preferably in the range of 88% or more. The higher the void reduction rate after 1 to 5 minutes, the easier it is for the voids in the yarn bundle of the glass cloth to be removed in the process of impregnating the glass cloth with resin as varnish or the process of processing the prepreg into a printed wiring board by heating and pressurizing, and it is possible to improve the adhesion between the glass cloth and the resin. By improving the adhesion between the glass cloth and the resin, it is possible to provide a printed wiring board having good insulation reliability and heat resistance even if the amount of surface treatment agent attached to the glass cloth surface is small. In order to achieve a void reduction rate of 70% or more after 1 to 5 minutes of impregnation with castor oil, for example, glass cloth is treated with a silane coupling agent represented by the above general formula (1) and then subjected to a fiber opening technique such as dry ice blasting or bending. The void reduction rate can be measured by the method described in the Examples.
[0048] [Method of manufacturing glass cloth] The first method for producing glass cloth according to the present embodiment includes a method for treating glass. The glass processing method according to the present embodiment includes the steps of: (A) reducing a sizing agent from a glass yarn having a bulk dielectric tangent of 0.0010 or less; A step (B) of reducing the silane coupling agent from the glass cloth so that the ignition loss value is 0.01% by mass or more and less than 0.12% by mass; A step (C) of opening the glass cloth so that the number of voids after 5 minutes of impregnating the glass cloth with castor oil is 180 or less; This makes it possible to provide a glass cloth and a prepreg that can improve the dielectric properties and the heat resistance of a printed wiring board.
[0049] The second method for producing glass cloth according to the present embodiment includes a method for treating glass. The glass processing method according to the present embodiment includes the steps of: (A) reducing a sizing agent from a glass yarn having a bulk dielectric tangent of 0.0010 or less; A step (B) of reducing the silane coupling agent from the glass cloth so that the ignition loss value is 0.01% by mass or more and less than 0.12% by mass; A step (C) of opening the glass cloth so that the void reduction rate after 1 minute to 5 minutes when the glass cloth is impregnated with castor oil is 70% or more; This makes it possible to provide a glass cloth and a prepreg that can improve the dielectric properties and the heat resistance of a printed wiring board.
[0050] The glass treatment method according to the present embodiment can be applied to glass yarns and also to glass cloth. In other words, the process of weaving glass yarns to obtain glass cloth may be performed before, during, or after the glass treatment method according to the present embodiment. Note that "reduction" in the glass treatment method according to the present embodiment means, for example, removing at least a part of the sizing agent or silane coupling agent, and the occurrence of residual substances that cannot be completely removed is permitted.
[0051] The step (A) of reducing the sizing agent may, for example, be The de-starching process (heat de-oiling process) involves heating the glass at temperatures between 650℃ and 1000℃. This makes it easier to reduce the amount of sizing agent from the glass. By reducing the amount of thermally oxidized degradation products of the minute amount of sizing agent remaining in a physically attached state on the glass surface, it becomes easier to effectively suppress an increase in the dielectric tangent of the resulting glass cloth.
[0052] The glass cloth can be heated sequentially or continuously in a closed or open system, or in a combination of a closed system and an open system. From the viewpoint of productivity, a method of heat-treating the glass cloth in a roll-to-roll manner using an apparatus having an unwinding mechanism and a winding mechanism is particularly preferred.
[0053] In the case of a closed system, it is preferable to place the glass cloth in a heating furnace from the viewpoint of the heating means, and / or it is preferable to heat the glass cloth while storing it in a rolled state from the viewpoint of storage space and heating range. It is also preferable to heat the glass cloth while conveying it in the heating furnace from the viewpoint of increasing the efficiency of organic matter removal and shortening the time required for removing organic matter.
[0054] In the case of an open system, it is preferable to heat the glass cloth while transporting it from the viewpoint of the heated area. The glass cloth can be transported, for example, by an unwinding mechanism and a winding mechanism.
[0055] [Heating furnace] The heating means for the heating furnace is not limited to a specific means and may be various means such as an electric heater or a burner as long as it can heat the glass cloth so that the surface temperature of the glass cloth reaches a temperature higher than 650° C. In addition, a combination of a plurality of means may be used for heating, but it is preferable to heat the glass cloth in an atmosphere with an oxygen concentration of 10% or more, and for this purpose, it is preferable to use a gas-type single radiant tube burner or an electric heater.
[0056] From the viewpoint of heating efficiency, the heating furnace is preferably equipped with a means for discharging gas generated in the heating furnace and / or an air circulation means. The gas discharge means may be, for example, a nozzle, a gas pipe, a small hole, a gas vent valve, etc. The air circulation means may be, for example, a fan, an air conditioning system, etc.
[0057] In addition, in order to efficiently remove organic matter adhering to the surface of the glass cloth, a continuous system capable of heating the glass cloth while continuously passing it through a heating furnace is preferable to a batch system in which a glass fiber fabric is wound around a core and the glass cloth is heated at a predetermined atmospheric temperature.
[0058] In order to sufficiently remove organic matter adhering to the surface of the glass cloth, the heating temperature is preferably a temperature at which the surface temperature of the glass cloth is higher than 650° C., more preferably 700° C. or higher, further preferably 750° C. or higher, and particularly preferably 800° C. or higher. The surface temperature of the glass cloth can be measured, for example, by a thermocouple, a non-contact thermometer, or the like.
[0059] [Contact member for heating glass cloth] The glass cloth may be heated using the above-mentioned heating furnace. From the viewpoint of low running costs, however, the glass cloth may be heated by contacting a member heated to a predetermined temperature with the glass cloth.
[0060] The shape of the contact member is not particularly limited as long as it can heat the glass cloth so that the surface temperature exceeds 650°C, but a roll shape is preferable because it is easy to transport the glass cloth. As a member capable of heating the glass cloth in a roll shape, a roll that can be used in a high temperature range and has relatively little temperature variation in the width direction and heats by an induction heating method is preferable. When the glass cloth is heated by the contact member, it is considered that the temperature of the contact member and the surface temperature of the glass cloth are approximately equal.
[0061] In addition, in order to remove charcoal adhering to the heating roll as the glass cloth is continuously heated, the above-mentioned heating roll method is preferably a method equipped with a mechanism for removing dirt and foreign matter adhering to the roll, such as a mechanism such as a blade.
[0062] The step (B) of attaching the silane coupling agent can be carried out, for example, as follows: A coating process in which a silane coupling agent is attached to the surface of the glass using a treatment liquid having a concentration of 0.1% by mass to 0.5% by mass; a fixing step of fixing the silane coupling agent to the surface of the glass by heating and drying; In order to reduce the silane coupling agent residue and modified substances that cannot be reduced by water, washing with a highly hydrophobic organic solvent or an organic solvent having a high affinity for the silane coupling agent residue and modified substances having a hydroxyl group is carried out after the fixing step, which makes it easier to perform a suitable surface treatment of the glass cloth.
[0063] Methods for applying the treatment liquid to the glass in the coating step include (a) a method in which the glass is immersed or passed through the treatment liquid stored in a bath (hereinafter referred to as the "immersion method"), and (b) a method in which the treatment liquid is applied to the glass using a roll coater, a die coater, a gravure coater, or the like. When the immersion method is adopted, it is preferable to select a time for immersing the glass in the treatment liquid of 0.5 seconds or more and 1 minute or less. In addition, after the treatment liquid is applied to the glass, the solvent contained in the treatment liquid can be heated and dried using a method such as hot air or electromagnetic waves.
[0064] The concentration of the treatment liquid is preferably 0.1% by mass to 0.5% by mass, more preferably 0.1% by mass to 0.45% by mass, and even more preferably 0.1% by mass to 0.4% by mass, which facilitates more suitable surface treatment of glass.
[0065] In the fixing step, the heating and drying temperature is preferably 80° C. or higher, more preferably 90° C. or higher, so that the reaction between the silane coupling agent and the glass is sufficiently carried out, and is preferably 300° C. or lower, more preferably 180° C. or lower, so as to prevent deterioration of the organic functional group of the silane coupling agent.
[0066] The silane coupling agent residue and modified substances can be removed by known methods such as immersion and shower spraying, and may be heated or cooled as necessary. In order to prevent the dissolved glass cloth deposits from re-adhering, it is preferable to reduce the excess solvent from the washed glass cloth using a squeeze roller or the like before finish drying. The organic solvent to be used is not particularly limited, but examples of highly hydrophobic organic solvents include: Saturated chain aliphatic hydrocarbons such as n-pentane, i-pentane, n-hexane, i-hexane, n-heptane, i-heptane, n-octane, i-octane, 2,2,4-trimethylpentane (isooctane), n-nonane, i-nonane, n-decane, i-decane, and 2,2,4,6,6-pentamethylheptane (isododecane); Saturated cyclic aliphatic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, and ethylcyclohexane; Aromatic hydrocarbons such as benzene, toluene, xylene, ethylbenzene, diethylbenzene, trimethylbenzene, and triethylbenzene; Halogen-containing solvents such as chloroform, dichloromethane, and dichloroethane; Examples of organic solvents having high affinity with the modified silane coupling agent include alcohols such as methanol, ethanol, and butanol, ketones such as acetone and methyl ethyl ketone, and ethers such as methyl ethyl ether and diethyl ether; Amides such as N,N-dimethylformamide and N,N-dimethylacetamide; dimethyl sulfoxide; etc. Among these, from the viewpoint of making the dielectric loss tangent of the obtained glass cloth close to the bulk dielectric loss tangent, aromatic hydrocarbons, alcohols, or ketones are preferred, and methanol is more preferred. Therefore, as the cleaning liquid in the finish cleaning step, it is preferred to use a cleaning liquid whose main component is methanol (methanol is 50 mass % or more, or 60 mass % or more relative to 100 mass % of the cleaning liquid).
[0067] In the finish drying step, the cleaning liquid used in the finish washing step can be reduced. From the viewpoint of easiness in reducing the amount of cleaning liquid by drying, the cleaning liquid used in the finish washing step preferably has a boiling point of 120°C or less. For drying, a method of heat drying or air blowing can be adopted. When an organic solvent is used as the cleaning liquid, it is preferable to perform heat drying by hot air drying using low pressure steam or heat transfer oil as a heat source from the viewpoint of safety. The drying temperature is preferably equal to or higher than the boiling point of the cleaning liquid, and is preferably equal to or lower than 180°C from the viewpoint of suppressing deterioration of the silane coupling agent.
[0068] The step (C) of opening the glass cloth may be, for example, an opening treatment in which the obtained glass cloth is subjected to pressure from a water flow; an opening treatment by high-frequency vibration using water (e.g., degassed water, ion-exchanged water, deionized water, electrolytic cation water, electrolytic anion water, etc.) as a medium; a processing treatment by pressurization with a roll; a processing by dry ice blast; a processing by bending with a small radius of curvature, etc. Such opening treatment may be performed simultaneously with weaving or after weaving. It may be performed before or after heat cleaning or simultaneously with heat cleaning, or it may be performed simultaneously with or after the surface treatment step (B). From the viewpoint of controlling the number of voids 5 minutes after impregnation with castor oil and the void reduction rate 1 minute to 5 minutes after impregnation with castor oil, it is necessary to increase the processing force in the opening step, and dry ice blast processing or bending processing is preferable as a method of opening glass cloth composed of glass yarns with high glass hardness.
[0069] Dry ice blasting is a method of spraying (blowing) dry ice particles with a particle size of 5 to 300 μm from a height of 5 to 1000 mm with an air pressure of 0.05 to 1 MPa. More preferably, dry ice particles with a particle size of 5 to 300 μm are sprayed from a height of 5 mm to 600 mm with an air pressure of 0.1 to 0.5 MPa. By keeping the spraying amount within this range, it is expected to have the effect of improving impregnation without causing quality problems such as broken glass fibers.
[0070] The bending process is a method of opening the filaments by passing them through a roll having a radius of curvature R of 2.5 mm or less, preferably a radius of curvature R of 2.0 mm or less, two or more times, preferably ten or more times. If the radius of curvature R is 2.5 mm or less, the filaments can be sufficiently peeled off from each other by the sizing agent or run coupling agent, and the effect of improving impregnation is likely to be achieved.
[0071] The method for producing the glass cloth according to the present embodiment includes the steps of: A weaving process in which glass yarn is woven to obtain glass cloth; The method for producing a glass cloth according to the present embodiment may include a weaving step before the covering step, may include a weaving step between the covering step and the finish washing step, or may include a weaving step after the finish washing step.
[0072] In addition, the method for producing the glass cloth according to the present embodiment may further include, as necessary, a residual sizing agent reduction step for reducing modified substances of the sizing agent remaining in the desizing step; After the weaving process, a spreading process is performed to spread the glass yarns of the glass cloth. The method may include at least one of the steps.
[0073] In the adhesive residue reduction step, dry cleaning such as plasma irradiation, UV ozone, etc., wet cleaning such as high-pressure water washing, organic solvent washing, nanobubble water washing, ultrasonic water washing, etc., and heat cleaning at a higher temperature than in the thermal desizing step can be performed, or a combination of these may be used. In particular, in the adhesive residue reduction step, it is preferable to perform short-time heat cleaning in which the glass yarn or glass cloth is passed from roll to roll through a heating furnace at 800°C or higher.
[0074] According to the manufacturing method of the glass cloth according to the present embodiment described above, it is possible to suitably reduce unnecessary components that are considered to increase the dielectric tangent, and to easily apply a silane coupling agent to the surface of each glass filament that constitutes the glass yarn. In addition, by strengthening the opening treatment of the glass fibers, it is possible to improve the heat resistance and insulation reliability of the printed wiring board.
[0075] [Prepreg] The prepreg according to the present embodiment contains the above-mentioned glass cloth and a matrix resin impregnated into the glass cloth, thereby making it possible to provide a prepreg with few voids.
[0076] The matrix resin may be a thermosetting resin or a thermoplastic resin. If possible, both may be used in combination, or may further contain other resins.
[0077] Examples of thermosetting resins include: (a) an epoxy resin obtained by reacting and curing a compound having an epoxy group with a compound having at least one group reactive with the epoxy group selected from the group consisting of an amino group, a phenol group, an acid anhydride group, a hydrazide group, an isocyanate group, a cyanate group, and a hydroxyl group; (b) a radical polymerization type curable resin obtained by curing a compound having at least one group selected from the group consisting of an allyl group, a methacryl group, and an acrylic group; (c) a maleimide triazine resin obtained by reacting and curing a compound having a cyanate group with a compound having a maleimide group; (d) a thermosetting polyimide resin obtained by reacting and curing a maleimide compound with an amine compound; (e) a benzoxazine resin obtained by crosslinking and curing a compound having a benzoxazine ring through thermal polymerization; Examples include. In (a) obtaining an epoxy resin, the compounds can be reacted without a catalyst, or the compounds can be reacted by adding a catalyst having a reaction catalytic ability, such as an imidazole compound, a tertiary amine compound, a urea compound, or a phosphorus compound. In (b) obtaining a radical polymerization type cured resin, a thermal decomposition type catalyst or a photodecomposition type catalyst can be used as a reaction initiator.
[0078] Examples of thermoplastic resins include polyphenylene ether, modified polyphenylene ether, polyphenylene sulfide, polysulfone, polyether sulfone, polyarylate, aromatic polyamide, polyether ether ketone, thermoplastic polyimide, insoluble polyimide, polyamide imide, and fluororesin. As an insulating material for printed wiring boards for high-speed communication, polyphenylene ether or modified polyphenylene ether, which has high radical reactivity, is preferable.
[0079] When the matrix resin used in a printed wiring board for high-speed communication has a vinyl group or a methacryl group, a silane coupling agent that has a relatively high hydrophobicity and a functional group involved in a radical reaction, such as a methacryl group, is compatible with the matrix resin.
[0080] As described above, the thermosetting resin and the thermoplastic resin can be used in combination. The prepreg can further contain an inorganic filler. The inorganic filler is preferably used in combination with the thermosetting resin, and examples of the inorganic filler include aluminum hydroxide, zirconium oxide, calcium carbonate, alumina, mica, aluminum carbonate, magnesium silicate, aluminum silicate, silica, talc, short glass fibers, aluminum borate, and silicon carbide. The inorganic filler may be used alone or in combination of two or more kinds.
[0081] [Printed wiring board] The printed wiring board according to the present embodiment contains the prepreg, which makes it possible to provide a printed wiring board with excellent insulation reliability.
[0082] [Integrated circuits and electronic devices] An integrated circuit and an electronic device including the printed wiring board according to the present embodiment are also an aspect of the present embodiment. The integrated circuit and the electronic device obtained by using the printed wiring board according to the present embodiment are excellent in various properties. EXAMPLES
[0083] The present invention will now be described in detail with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0084] [Method of measuring basis weight (mass of cloth)] The cloth was cut to a predetermined size, and the mass was divided by the sample area. 2 The weight of each glass cloth was calculated by cutting the cloth into pieces of a size of 100 mm and measuring the mass.
[0085] [Method of measuring converted thickness] Since the glass cloth is a discontinuous planar body with air between the glass fibers, the converted thickness was calculated by dividing the basis weight (mass of the cloth) of each glass cloth by its density. Specifically, the converted thickness was calculated using the following formula (3): Converted thickness (μm) = basis weight (g / m 2 )÷Density(g / cm 3 ) ···(3) The converted thickness was calculated by the above method. This converted thickness was used for the measurement by the resonance method.
[0086] [Method of measuring dielectric tangent] The dielectric loss tangent of each glass cloth was determined in accordance with IEC 62562. Specifically, the glass cloth sample was sampled to a size required for measurement with a split cylinder resonator and stored in a thermo-hygrostatic oven at 23°C and 50% RH for 8 hours or more. The dielectric properties of the stored sample were measured using a split cylinder resonator (manufactured by EM Lab) and an impedance analyzer (manufactured by Agilent Technologies). The measurement was performed five times for each sample, and the average value was calculated. The thickness of each sample was measured using the above-mentioned converted thickness. Similarly, a glass plate having a thickness of 300 μm or less and having the same composition as each glass cloth was prepared, and the bulk dielectric loss tangent was also measured from the thickness value obtained by measuring the thickness of the glass plate. Note that IEC 62562 mainly specifies a method for measuring the dielectric properties of fine ceramic materials used in microwave circuits in the microwave band.
[0087] [Method for measuring ignition loss of glass cloth] The ignition loss value of the glass loss was determined in accordance with JIS R3420.
[0088] [Method of measuring nitrogen content] The surface-treated glass cloth was heated at approximately 800°C for 1 minute, and the amount of nitrogen dioxide in the generated gas was measured by gas chromatography to determine the amount of nitrogen dioxide in the generated gas. The nitrogen content (mass%) per mass of the glass cloth contained in the surface-treated glass cloth was determined by comparing the amount of nitrogen dioxide generated when a predetermined amount of acetanilide (C8H9NO) was similarly heated at approximately 800°C for 1 minute in advance. A SUMIGRAPH NC-90A (manufactured by Sumika Chemical Analysis Center) was used for the measurement. Molecular weight of acetanilide = 135.17 Nitrogen percentage of acetanilide = 10.36%
[0089] That is, the nitrogen content per mass of the glass cloth was calculated based on the following formula. Nitrogen content per mass of glass cloth = [{mass of acetanilide × (nitrogen ratio in acetanilide / 100)} / peak area due to nitrogen dioxide generated from acetanilide] × {(peak area of nitrogen dioxide generated from glass cloth / mass of glass cloth) × 100}
[0090] [Method of measuring impregnation] The glass cloth was sampled to a size of 50 mm x 50 mm or more. At this time, the sample was sampled without bending or touching the measurement area. The sampled glass cloth was impregnated with castor oil (manufactured by Hayashi Pure Chemical Industries Co., Ltd.) at a liquid temperature of 24 to 26 ° C. for a predetermined time, and the number of voids was counted to evaluate. A high-precision camera (frame size: 5120 x 5120 pixels) was installed at a position perpendicular to the glass cloth, and an LED light (power flash bar type lighting manufactured by CCS Co., Ltd.) was used as a light source, and was irradiated from both sides so as to sandwich the glass cloth from a position directly to the side 15 cm away from the glass cloth. Then, in a 32 mm x 32 mm viewing angle, the number of voids of 160 μm or more present between the glass filaments was counted, and the average value of three measurements was taken as the number of voids. The voids correspond to the parts not impregnated with the matrix resin. Therefore, a small number of voids in a glass cloth means that the glass cloth has excellent impregnation with the matrix resin.
[0091] Here, the "void reduction rate (%) after 1 minute to 5 minutes when impregnated with castor oil" is The number of voids in the glass cloth when it is soaked in castor oil for 1 minute is defined as A. If the number of voids in the glass cloth after immersion in castor oil for 5 minutes is B, It is calculated using the formula "{(AB) / A}×100(%)".
[0092] [Glass cloth] (grey A) A cloth was woven using glass yarns with a SiO2 content of more than 99.9% by mass at a weaving density of 66 warp yarns / 25 mm and 68 weft yarns / 25 mm using an air jet loom. The warp yarns were made of silica glass with an average filament diameter of 5.0 μm, 100 filaments, and a twist of 1.0Z. The weft yarns were made of silica glass with an average filament diameter of 5.0 μm, 100 filaments, and a twist of 1.0Z.
[0093] (grey B) A cloth was woven using an air jet loom with a weaving density of 54 warp threads / 25 mm and 54 weft threads / 25 mm using glass yarns with a SiO2 content of more than 99.9% by mass. The cloth was woven to a width of 1300 mm. As the warp threads, silica glass yarns with an average filament diameter of 5.0 μm, 200 filaments, and 1.0Z twist were used. As the weft threads, silica glass yarns with an average filament diameter of 5.0 μm, 200 filaments, and 1.0Z twist were used.
[0094] (grey C) A cloth was woven using E-glass yarn with a weaving density of 66 warp threads / 25 mm and 68 weft threads / 25 mm. The warp threads were E-glass yarns with an average filament diameter of 5.0 μm, 100 filaments, and 1.0Z twist. The weft threads were E-glass yarns with an average filament diameter of 5.0 μm, 100 filaments, and 1.0Z twist.
[0095] Example 1 The greige fabric A was heat-treated at 900°C for 60 seconds to remove the size (thermal de-oiling process). Next, a treatment liquid was prepared by dispersing 0.3 mass% of 3-methacryloxypropyltrimethoxysilane (silane coupling agent A); Z6030 (Dow-Toray) in pure water adjusted to pH = 3 with acetic acid. The cloth was immersed in the treatment liquid at a line speed of 1.5 m / min, and after squeezing out the liquid, it was heated and dried at 130°C for 60 seconds to fix the silane coupling agent (fixing process). The dried cloth was then immersed in water at a frequency of 25 kHz and an output of 0.50 W / cm. 2The excess silane coupling agent that had physically adhered to the cloth was reduced by irradiating it with ultrasonic waves (cleaning process), and then it was dried at 130°C for 1 minute (drying process). After that, 5-50μm dry ice particles were sprayed uniformly over the entire glass cloth with an air pressure of 0.4MPa to perform an opening process (opening process by dry ice blasting) to obtain glass cloth. The converted thickness was calculated from the basis weight and density of the obtained glass cloth, and the dielectric loss tangent of the glass cloth was measured.
[0096] Example 2 The greige cloth A was heat-treated at 600°C for 60 seconds to remove the size. Next, a treatment liquid was prepared by dispersing 0.1 mass% of 3-methacryloxypropyltrimethoxysilane (silane coupling agent A); Z6030 (Dow-Toray) in pure water adjusted to pH = 3 with acetic acid. The cloth was immersed in the treatment liquid at a line speed of 1.5 m / min, squeezed out, and then heated and dried at 130°C for 60 seconds to fix the silane coupling agent. The dried cloth was then immersed in water at a frequency of 25 kHz and an output of 0.50 W / cm. 2 The excess silane coupling agent that had physically adhered to the cloth was reduced by irradiating it with ultrasonic waves, and then it was dried at 130°C for 1 minute. After that, 5-50μm dry ice particles were sprayed uniformly over the entire glass cloth with an air pressure of 0.5MPa to perform an opening process, thereby obtaining a glass cloth. The converted thickness was calculated from the basis weight and density of the obtained glass cloth, and then the dielectric loss tangent of the glass cloth was measured.
[0097] Example 3 The greige fabric A was heat-treated at 900°C for 60 seconds to remove the size. Next, a treatment liquid was prepared by dispersing 0.3 mass% of 5-hexenyltrimethoxysilane (silane coupling agent B); Z6161 (Dow Toray) in pure water adjusted to pH = 3 with acetic acid. The cloth was immersed in the treatment liquid at a line speed of 1.5 m / min, squeezed out, and then heated and dried at 130°C for 60 seconds to fix the silane coupling agent. The dried cloth was then immersed in water at a frequency of 25 kHz and an output of 0.50 W / cm. 2The excess silane coupling agent that had physically adhered to the cloth was reduced by irradiating it with ultrasonic waves, and then it was dried at 130°C for 1 minute. After that, dry ice particles of 5 to 50 μm were sprayed uniformly over the entire glass cloth with an air pressure of 0.5 MPa to perform an opening process, thereby obtaining a glass cloth. The converted thickness of the obtained glass cloth was calculated from the basis weight and density, and then the dielectric loss tangent of the glass cloth was measured.
[0098] Example 4 The greige cloth A was heat-treated at 900°C for 60 seconds to remove the size. Next, a treatment liquid was prepared by dispersing 0.15% by mass of 3-methacryloxypropyltrimethoxysilane (silane coupling agent A); Z6030 (manufactured by Dow Toray Co., Ltd.) and 0.15% by mass of 5-hexenyltrimethoxysilane (silane coupling agent B); Z6161 (manufactured by Dow Toray Co., Ltd.) in pure water adjusted to pH = 3 with acetic acid. The cloth was immersed in the treatment liquid at a line speed of 1.5 m / min, squeezed out, and then heated and dried at 130°C for 60 seconds to fix the silane coupling agent. The dried cloth was then immersed in water at a frequency of 25 kHz and an output of 0.50 W / cm. 2 The excess silane coupling agent that had physically adhered to the cloth was reduced by irradiating it with ultrasonic waves, and then it was dried at 130°C for 1 minute. After that, 5-50μm dry ice particles were sprayed uniformly over the entire glass cloth with an air pressure of 0.2MPa to perform an opening process, thereby obtaining a glass cloth. The converted thickness of the obtained glass cloth was calculated from the basis weight and density, and then the dielectric loss tangent of the glass cloth was measured.
[0099] Example 5 A glass cloth was obtained in the same manner as in Example 1, except that the solvent used in the ultrasonic cleaning was changed from water to methanol. The converted thickness of the obtained glass cloth was calculated from the basis weight and density of the glass cloth, and then the dielectric loss tangent of the glass cloth was measured.
[0100] Example 6 The greige B was heat-treated at 1000°C for 20 seconds to remove the size. Next, a treatment liquid was prepared by dispersing 0.15 mass% of 3-methacryloxypropyltrimethoxysilane (silane coupling agent A); Z6030 (Dow Toray) in pure water adjusted to pH = 3 with acetic acid. The cloth was immersed in the treatment liquid at a line speed of 1.5 m / min, squeezed out, and then heated and dried at 130°C for 60 seconds to fix the silane coupling agent. The dried cloth was then soaked in a methanol solvent at a frequency of 25 kHz and an output of 0.50 W / cm. 2 The excess silane coupling agent physically attached to the cloth was reduced by irradiating it with ultrasonic waves, and then it was dried at 130°C for 1 minute. After that, 5 to 50 μm dry ice particles were sprayed uniformly over the entire glass cloth with an air pressure of 0.45 MPa to perform an opening process, thereby obtaining a glass cloth. The converted thickness was calculated from the basis weight and density of the obtained glass cloth, and then the dielectric loss tangent of the glass cloth was measured.
[0101] Comparative Example 1 Except for changing the concentration of the treatment liquid to 0.7% by mass and not carrying out the opening treatment by dry ice blasting, a glass cloth was obtained in the same manner as in Example 1. The converted thickness was calculated from the basis weight and density of the obtained glass cloth, and then the dielectric loss tangent of the glass cloth was measured.
[0102] Comparative Example 2 A glass cloth was obtained in the same manner as in Example 1, except that the concentration of the treatment liquid was 0.04% by mass and that the fiber-opening treatment by dry ice blasting was not performed. The converted thickness of the obtained glass cloth was calculated from the basis weight and density, and then the dielectric loss tangent of the glass cloth was measured.
[0103] Comparative Example 3 A glass cloth was obtained in the same manner as in Example 1, except that a treatment liquid in which 0.15 mass % of N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride (silane coupling agent C); Z6032 (manufactured by Toray Dow Corning Co., Ltd.) was dispersed was used, and the fiber opening treatment by dry ice blasting was not performed. The converted thickness was calculated from the basis weight and density of the obtained glass cloth, and then the dielectric loss tangent of the glass cloth was measured.
[0104] Comparative Example 4 A glass cloth was obtained in the same manner as in Comparative Example 3, except that the concentration of the treatment liquid was 0.35% by mass and that the fiber-opening treatment by dry ice blasting was not performed. The converted thickness was calculated from the basis weight and density of the obtained glass cloth, and then the dielectric loss tangent of the glass cloth was measured.
[0105] Comparative Example 5 A glass cloth was obtained in the same manner as in Example 1, except that the glass cloth was opened using a columnar flow discharged from a 1.4 MPa high-pressure water spray. The converted thickness of the obtained glass cloth was calculated from the basis weight and density, and then the dielectric loss tangent of the glass cloth was measured.
[0106] Comparative Example 6 A glass cloth was obtained in the same manner as in Example 1, except that greige fabric C was used and that thermal deoiling was performed at 400° C. for 72 hours. The converted thickness was calculated from the basis weight and density of the obtained glass cloth, and then the dielectric loss tangent of the glass cloth was measured.
[0107] [Method of manufacturing laminate] To the glass cloth obtained in the Examples and Comparative Examples, 45 parts by mass of polyphenylene ether (SABIC, SA9000), 10 parts by mass of triallyl isocyanurate, 45 parts by mass of toluene, and 0.6 parts by mass of 1,3-di(tert-butylisopropylbenzene) were added to a stainless steel container, and the mixture was stirred at room temperature for 1 hour to prepare a varnish. The glass cloth was impregnated with the prepared varnish, and then dried at 115°C for 1 minute to obtain a prepreg. Eight sheets of the obtained prepreg were stacked, and copper foils with a thickness of 12 μm were further stacked on top and bottom, and the mixture was heated at 200°C and 40 kg / cm2 The mixture was heated and pressed at 400° C. for 120 minutes to obtain a laminate.
[0108] [Method of evaluating heat resistance of laminate] After removing the copper foil from the laminate obtained as described above, the laminate was heated and absorbed water in a pressure cooker at 133°C for 62 hours. Furthermore, the laminate after absorbing water was immersed in a solder bath at 288°C for 20 seconds, and visually checked for the presence or absence of swelling (blistering) due to peeling at the interface between the glass cloth and the resin. Four tests were performed for each glass cloth. In Table 2, the heat resistance was evaluated as follows. The less the glass cloth blistered, the more excellent the heat resistance. E (◯): Of the four laminates, none showed any blister. G (△): Blisters were observed in one or two laminates. P(x): Blisters were observed in 3 or 4 laminates.
[0109] [Method of evaluating the insulation reliability of laminates] A laminate was prepared as described above to a thickness of 1.0 mm, and a wiring pattern with through holes spaced 0.30 mm apart was prepared on the copper foil on both sides of the laminate to obtain a sample for evaluating insulation reliability. A voltage of 50 V was applied to the obtained sample in an atmosphere of a temperature of 85°C and a humidity of 85% RH, and the change in resistance value was measured. In this case, a case in which the resistance became less than 1 MΩ within 500 hours after the start of the test was counted as an insulation failure. The same measurement was performed on 10 samples, and the number of samples that did not have an insulation failure out of the 10 samples was calculated.
[0110] The production conditions and evaluation results of the Examples and Comparative Examples are shown in Table 2. Note that, for all of the glass cloths of Examples 1 to 6, prepregs and printed wiring boards could be produced by standard methods.
[0111] [Table 2]
Claims
1. A glass cloth made by weaving glass yarn, The bulk dielectric tangent of the glass constituting the glass yarn is 0.0010 or less; The ignition loss value of the glass cloth is 0.01% by mass or more and less than 0.12% by mass, A glass cloth having a void count of 180 or less as measured by the following method. (1) The sampled glass cloth is immersed in castor oil (manufactured by Hayashi Pure Chemical Industries, Ltd.) at a liquid temperature of 24° C. for 5 minutes. (2) Within a viewing angle of 32 mm×32 mm, the number of voids of 160 μm or more is counted.
2. 2. The glass cloth according to claim 1, wherein the glass cloth has a void reduction rate of 70% or more after 1 to 5 minutes from impregnation with castor oil.
3. A glass cloth made by weaving glass yarn, The bulk dielectric tangent of the glass constituting the glass yarn is 0.0010 or less; The ignition loss value of the glass cloth is 0.01% by mass or more and less than 0.12% by mass, A glass cloth having a void reduction rate of 70% or more as measured by the following method. (1) The sampled glass cloth is immersed in castor oil (manufactured by Hayashi Pure Chemical Industries, Ltd.) at a liquid temperature of 24° C. for 1 minute or for 5 minutes. (2) In a 32 mm x 32 mm viewing angle, the number of voids of 160 μm or more is counted, and the number of voids when the impregnation is carried out after 1 minute is designated as A, and the number of voids when the impregnation is carried out after 5 minutes is designated as B. (3) The following formula: {(AB) / A}×100(%) The void reduction rate is calculated from the above.
4. 2. The glass cloth according to claim 1, wherein the number of voids in the glass cloth after 5 minutes of being impregnated with castor oil is 160 or less.
5. 4. The glass cloth according to claim 2, wherein the void reduction rate of the glass cloth after 1 to 5 minutes from impregnation with castor oil is 80% or more.
6. 4. The glass cloth according to claim 1, wherein the bulk dielectric tangent of the glass constituting the glass yarns is 0.0008 or less.
7. The silicon (Si) content in the glass yarn is silicon dioxide (SiO 2 The glass cloth according to claim 1 or 3, wherein the total mass of the glass fiber is 95.0 mass % to 100 mass % in terms of the total mass of the glass fiber.
8. The silicon (Si) content in the glass yarn is silicon dioxide (SiO 2 The glass cloth according to claim 1 or 3, wherein the content is 99.0 mass% to 100 mass% in terms of the total mass of the glass fiber.
9. 4. The glass cloth according to claim 1 or 3, which has been surface-treated.
10. The surface treatment is carried out according to the following general formula (1): X (R) 3-n Yes n ・・・(1) (In the formula, X is an organic functional group having one or more unsaturated double bond groups having radical reactivity, Each Y is independently an alkoxy group; n is an integer from 1 to 3, Each R is independently at least one group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group.
10. The glass cloth according to claim 9, which is treated with a silane coupling agent having a structure represented by the formula:
11. 11. The glass cloth according to claim 10, wherein X in the general formula (1) does not contain an amino group and has a (meth)acryloxy group.
12. The glass cloth according to claim 1 or 3, wherein the glass cloth has an ignition loss value of 0.10 mass % or less.
13. 4. The glass cloth according to claim 1, having a nitrogen content per mass of less than 0.004 mass%.
14. 4. The glass cloth according to claim 1, wherein the dielectric loss tangent of the glass cloth at 10 GHz measured by a resonance method is more than 0 and not more than 0.0008.
15. 4. The glass cloth according to claim 1, which has a dielectric loss tangent at 10 GHz, measured by a resonance method, of more than 0 and not more than 0.0005.
16. A prepreg comprising the glass cloth according to claim 1 or 3 and a matrix resin impregnated into the glass cloth.
17. 17. The prepreg of claim 16, further comprising an inorganic filler.
18. A printed wiring board comprising the prepreg of claim 16.
19. 20. An integrated circuit comprising the printed wiring board of claim 18.
20. An electronic device comprising the printed wiring board according to claim 18.
Citation Information
Patent Citations
Synchronizer ring
JP1993001723A
Method and apparatus for impregnating woven fabric base material with varnish
JP1999188728A
Quartz glass cloth
JP2009263824A
Sizing agent for quartz glass fiber, quartz glass fiber, quartz glass yarn and quartz glass cloth
JP2016098135A
Glass cloth, prepreg and printed wiring board
JP2018127747A